(untitled) (Journal of the College of Basic Education, 2022)
The beauty of Islamic Sharia Law is that it encompasses all aspects of life and takes important ‎position on every single matter.One important matter is how Muslims should deal with their non-‎Muslim relatives. This issue has origin in the Personal Status Law and in Transactions Law and the ‎Islamic jurisprudence has covered all that as we study in this research.‎